2008
DOI: 10.1111/j.1541-4329.2008.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Discussions with Student‐Led Feedback: a Useful Activity to Enhance Development of Critical Thinking Skills

Abstract: Critical thinking skills (CTS) are the core learning outcome measures for higher education. Generally, CTS are not extensively developed or practiced during primary and secondary education. As such, early cultivation of CTS is essential for mastery prior to collegiate matriculation. Weekly engagement in 50 min of classroom discussion with student feedback (CDSF) was utilized to develop the CTS of students in an introductory food science course at Purdue Univ. Students' critical thinking ability was assessed lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 10 publications
2
20
0
Order By: Relevance
“…Where such opportunities are provided, it is evident that large numbers of students do not make use of such opportunities. There is some consensus suggesting students prefer individual to group feedback (Cramp, 2011), although studies also point to the benefits of group discussion (Hayes & Devitt, 2008). There is less consensus and detail within the literature on how principles of effective feedback can be applied to practice within and across different subject domains (Crossouard & Pryor, 2009).…”
Section: Tablementioning
confidence: 99%
“…Where such opportunities are provided, it is evident that large numbers of students do not make use of such opportunities. There is some consensus suggesting students prefer individual to group feedback (Cramp, 2011), although studies also point to the benefits of group discussion (Hayes & Devitt, 2008). There is less consensus and detail within the literature on how principles of effective feedback can be applied to practice within and across different subject domains (Crossouard & Pryor, 2009).…”
Section: Tablementioning
confidence: 99%
“…Different teaching strategies produce different effects on the development of critical thinking skills due to the interplay of various factors in tertiary education; for instance, learners, teaching and learning settings, and curriculum (Pithers & Soden, 2000). For different learners with different learning styles in different educational contexts, empirical studies have reported the positive effects of group discussion (Hayes & Devitt, 2008;Hudgins & Edelman, 1986;Schindler & Burkholder, 2014), concept mapping (Khodadady & Ghanizadeh, 2011;Lee et al, 2012;Wang & Liao, 2014), and analytical questioning (Alexander, Commander, Greenberg, & Ward, 2010;Barnett & Francis, 2011) on the development of critical thinking skills. However, learners' voice and learning experiences are seldom reported in these studies when exploring the effectiveness of teaching strategies in the improvement of critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…These steps include identify the issue, think about the goal, brainstorm possible solutions, think through possible results, try one of the solutions, and finally, evaluate the outcome. However, Hayes and Devitt (2008) indicated that in early learners, critical thinking strategies are not extensively developed or practiced during primary and secondary education. Teachers are therefore, obligated to help students develop the skills necessary to synthesize the nuances of a modern, complex society.…”
Section: Literature Reviewmentioning
confidence: 99%